2008
DOI: 10.1515/cog.2008.005
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic and metalinguistic categories in second language learning

Abstract: This paper discusses proposed characteristics of implicit linguistic and explicit metalinguistic knowledge representations as well as the properties of implicit and explicit processes believed to operate on these representations. In accordance with assumptions made in the usage-based approach to language and language acquisition, it is assumed that implicit linguistic knowledge is represented in terms of flexible and context-dependent categories which are subject to similarity-based processing. It is suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 65 publications
3
27
0
Order By: Relevance
“…Naturally, it should be easier for learners to associate an L2 word with other L2 vocabulary if they have more words in their mental lexicons to make reference to. This finding is also in keeping with the idea that increased proficiency in the L2 results in a higher level of metalinguistic awareness (Jessner, 1999;Ringbom, 1987;Roehr, 2008), and as such also in a heightened ability to elaborate on L2 vocabulary.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Naturally, it should be easier for learners to associate an L2 word with other L2 vocabulary if they have more words in their mental lexicons to make reference to. This finding is also in keeping with the idea that increased proficiency in the L2 results in a higher level of metalinguistic awareness (Jessner, 1999;Ringbom, 1987;Roehr, 2008), and as such also in a heightened ability to elaborate on L2 vocabulary.…”
Section: Discussionsupporting
confidence: 88%
“…If a learner's L2 proficiency can be considered to be an element of prior linguistic knowledge, research has indeed shown that, as a learner becomes more proficient in an L2 or L3, his/her level of metalinguistic awareness will increase (Jessner, 1999;Ringbom, 1987;Roehr, 2008). Jessner (2006, p. 42) defines metalinguistic awareness as 'the ability to focus attention on language as an object in itself or to think abstractly about language and, consequently, to play with or manipulate language'.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations